Short-delay multipath mitigation for indoor positioning applications - Zhang, Zhen (2008)
The works presented in this thesis mainly focus on mitigating short-delay multipath signals to enhance the ranging accuracy for Global Positioning System. The background behind this research is that nowadays GPS is widely used in urban areas and is being extended to indoor environments, where multipath signals are present. The multipath signals received by receiver antenna can degrade the C/A code ranging accuracy, and thus have significant effect on the estimation of user position. The existing techniques are able to mitigate the long-delay multipath signals quite well, but are less efficient in mitigating short-delay multipath signals which are numerous in urban areas and indoor environments.